Effect of Sofosbuvir on Length of Hospital Stay in Moderate COVID-19 Cases; a Randomized Controlled Trial - Bozorgmehr, Rama; Amiri, Farbod; Hosein Zade, Mohammad; Ghorbani, Fariba; Khameneh Bagheri, Arash; Yazdi, Esmat; Nekooghadam, Sayyed Mojtaba; Pourdowlat, Guitti; Fatemi, Alireza (Archives of Academic Emergency Medicine, 2022)
Introduction: Efforts to control the COVID-19 pandemic are still on. This study aimed to evaluate the effect of sofosbuvir on length of hospital stay and complications in COVID-19 cases with moderate severity. Methods: This randomized clinical trial was done on moderate COVID-19 cases, who were admitted to Shohadaye Tajrish Hospital, Tehran, Iran, from 4/2021 to 9/2021. Eligible patients were randomly allocated into two groups of intervention (sofosbuvir) and control, and their outcomes were compared regarding the length of hospital stay and complications. Results: 100 COVID-19 cases were randomly divided into two groups of 50 patients, as the intervention and control groups. The mean age of patients was 50.56 ± 12.23 and 57.1±14.1 years in the intervention and control groups, respectively (p = 0.02). The two groups were similar regarding distribution of gender (p = 0.15), underlying diseases (p = 0.08), the severity of COVID-19 (p = 0.80) at the time of admission, signs and symptoms (p > 0.05), and essential laboratory profile (p > 0.05). The length of hospital stay in the control and intervention groups was 7.7 ± 4.09 days and 4.7±1.6 days, respectively (p = 0.02). None of our patients needed ICU or mechanical ventilation. Conclusion: Sofosbuvir may decrease the length of hospital stay of COVID-19 cases with moderate severity, without a significant effect on the rate of intensive care unit (ICU) need and mortality.